Sociobioloģiskās (biokulturālās) Reliģijas Teorijas Un "Dieva Dzimšanas" Teoloģija: Sociobiological (Biocultural) Theories of Religion and the "Birth of God" Theology. - Titāns, Normunds (Cel̜š, 2016)
The article first outlines some basic tenets of cognitive science of religion (CSR), particularly from its "sociobiological" (or "biocultural") subfield. On the biological part, religion is conceived as shared imaginative engagement with supernatural agents having resulted from integration of evolutionary-cognitive mechanisms for detecting and dealing with natural agents. Theogony in this approach is explained by hyperactive detection of agency when humans are confronted with ambiguous phenomena. On the sociological part, in turn, religion is perpetuated by evolved socially-coalitional mechanisms for protection and cohesion of social (religious) groups that have been formed around such supernatural agents after their institutionalisation. Usually these explanations of religion are reductive, ruling out any supernatural causes, and theology is thereby rendered superfluous. In this situation, the approach of F. LeRon Shults - a Norwegian theologian, who has converted into atheism due to these naturalistic and social explanations of religion - is very unusual indeed. He believes that theology is still necessary and construes an atheistic theology of the "birth of God" based on the findings of sociobiology. The rest of the article, accordingly, tries to make sense of Shults' theology and, in conclusion, questions its adequacy, validity and consistency.